2020
DOI: 10.1186/s12864-020-6645-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leaf transcriptome in response to Rhizoctonia solani infection between resistant and susceptible rice cultivars

Abstract: Background: Sheath blight (SB), caused by Rhizoctonia solani, is a common rice disease worldwide. Currently, rice cultivars with robust resistance to R. solani are still lacking. To provide theoretic basis for molecular breeding of R. solani-resistant rice cultivars, the changes of transcriptome profiles in response to R. solani infection were compared between a moderate resistant cultivar (Yanhui-888, YH) and a susceptible cultivar (Jingang-30, JG). Results: In the present study, 3085 differentially express g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 70 publications
5
28
1
Order By: Relevance
“…Yang et al (2015) suggested that MPKs are transcriptionally responsive to Xoo infection and that these genes may be directly or indirectly involved in rice–pathogen interactions (Yang et al 2015). Recently, a study by Shi et al (2020) revealed that a greater number of MAPK signaling pathway genes were down‐regulated in a susceptible cultivar (Jingang‐30) compared to a moderately resistant cultivar (Yanhui‐888), which likely enhanced the susceptibility of the Jingang‐30 cultivar to rice sheath blight caused by Rhizoctonia solani .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2015) suggested that MPKs are transcriptionally responsive to Xoo infection and that these genes may be directly or indirectly involved in rice–pathogen interactions (Yang et al 2015). Recently, a study by Shi et al (2020) revealed that a greater number of MAPK signaling pathway genes were down‐regulated in a susceptible cultivar (Jingang‐30) compared to a moderately resistant cultivar (Yanhui‐888), which likely enhanced the susceptibility of the Jingang‐30 cultivar to rice sheath blight caused by Rhizoctonia solani .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the early stage of infection, plants prevent pathogen infection by enhancing cell wall lignification and producing a variety of secondary metabolites. Comprehensive KEGG enrichment analyses also indicate that phenylpropanoid and phenylalanine metabolism plays an important role in preventing infection in RSB resistant varieties (Kwon et al 2014 ; Shi et al 2020 ; Zhang et al 2017 ).…”
Section: Countermeasures From the Hostmentioning
confidence: 99%
“…The ethylene insensitive mutant sickle ( skl ) is highly susceptible to R. solani AG8, while the transgenic plants overexpressing ethylene response factors (ERFs) or the ethylene biosynthesis enzyme ACS2 exhibit resistance to R. solani (Anderson et al 2010 ; Anderson et al 2018 ; Helliwell et al 2013 ). Ethylene-insensitive protein 2 (EIN2) is significantly up-regulated in the resistant and susceptible rice varieties during R. solani infection (Shi et al 2020 ). These findings support that ethylene signaling positively regulates rice resistance to RSB.…”
Section: Countermeasures From the Hostmentioning
confidence: 99%
See 2 more Smart Citations